PERANAN PEUBAH PS1KOGRAFIS DALAM SEGMENTASI WISATAWAN - Ivantia Savitri Mokoginta (Bina Ekonomi, 1999)
This paper proposes the application of psychographic variable in tourists' segmentation. The Reason for proposing it is that this variable provides information about tourists’ preferences On destinations and object of interests. By using psychographic - in addition to trip Descriptors, demographic, geographic and behavioral variable - the information about the Profile of tourists in segmentation would have been sufficient.